SCENIC: INSTRUMEN EVALUASI KONTEKSTUAL BERBASIS SKENARIO UNTUK MEMPERKUAT KOMPETENSI MAHASISWA CALON GURU DALAM PROYEK STUDI KASUS - Intan Sari Rufiana; Anita Dewi Utami; Muhibuddin Fadhli; Mohammad Yusuf Randy; Fina Zulfa Mustafidah; Fierda Nursitasari Amaliya; Aulia Al Tsani Izzati (Universitas Muhammadiyah Ponorogo, 2026)
The evaluation of prospective teachers’ competencies during the pre-PPL phase still relies heavily on conventional instruments that fail to authentically assess their ability to solve classroom problems. In line with recent policies requiring case study projects in the PPG program, this article reports on the development of SCENIC (Scenario-based Contextual Evaluation for Nurturing Instructional Competence), a set of contextual scenario-based evaluation instruments integrated with case study projects. The research employed an R&D approach (Borg & Gall) through needs analysis, the design of seven scenarios, expert validation, and phased pilot testing with PPG students. The results indicate competency gaps in student needs analysis, inclusive learning design, and contextual communication; expert validation rated the content as relevant and highly applicable; and pilot testing showed that SCENIC helps calibrate performance assessments and strengthens students’ readiness to tackle case study assignments and UKIN/PPL. SCENIC is recommended as an authentic evaluation framework to bridge theory and practice in elementary teacher education.